The Correlation between Hormonal Disturbance in PCOS Women and Serum Level of Kisspeptin - Ibrahim, Razaw O. (Int J Endocrinol, 2020)
BACKGROUND: Kisspeptin is a neuropeptide that upregulates gonadotropin-releasing hormone (GnRH) secretion. It is an essential element for the luteinizing hormone (LH) surge and ovulation. Women with polycystic ovary syndrome (PCOS) expose alteration in both GnRH and LH secretion levels. OBJECTIVE: This paper aims to evaluate serum kisspeptin levels in healthy and polycystic ovarian syndrome women. Furthermore, it investigates the effect of obesity and age on circulating kisspeptin levels in both normal and PCOS women. Moreover, it points out the correlation between kisspeptin and other hormonal parameters. Methods and Patients. One hundred women (60 are with PCOS and 40 are normal) were enrolled in the study. Five milliliter samples of blood from all the patients and control women were obtained twice during the menstrual cycle. All the study samples were classified depending on the age factor for several subgroups. RESULTS: Kisspeptin levels were higher in PCOS patients than those in the normal group. Kisspeptin correlated with serum free testosterone level (r=0.26). In healthy women, preovulatory kisspeptin levels were higher than follicular kisspeptin levels (P < 0.05), while this difference was insignificant in PCOS patients. The variation in serum kisspeptin levels between overweight/obese and normal-weight women was insignificant. In normal women, serum kisspeptin levels were higher in women >35 years than those <24 years at (P=0.03). CONCLUSION: The serum kisspeptin level is higher in PCOS women. Its levels fluctuate during the menstrual cycle, but these fluctuations are disturbed in PCOS women. The effect of BMI on serum kisspeptin levels is insignificant, and kisspeptin serum levels increase with age.